Feeding Minds, Building Dignity: Indonesia’s Free Nutritious Meal Policy (MBG), Barriers, Prospects, and Policy Recommendations - Marzulina, Lenny; Mukminin, Amirul; Harto, Kasinyo (Edukasi, 2025)
This policy analysis examines Indonesia's ambitious Free Nutritious Meal Program (Program Makan Bergizi Gratis), launched in 2025 as a flagship initiative to address chronic malnutrition and stunting among children and pregnant women. The program aims to provide free nutritious meals to millions of beneficiaries across the archipelago, targeting improved health outcomes, enhanced educational performance, and long-term human capital development. Drawing on implementation science frameworks and comparative policy analysis, this paper identifies critical barriers to program success, including logistical challenges in remote and archipelagic regions, quality assurance across diverse socioeconomic contexts, inadequate infrastructure in participating schools and health facilities, and coordination complexities among multiple stakeholders spanning education, health, and agriculture sectors. The analysis reveals promising prospects grounded in Indonesia's existing social protection infrastructure, strong political commitment at the highest levels, potential for local economic stimulation through agricultural partnerships, and growing public awareness of nutrition's role in breaking intergenerational poverty cycles. However, sustainability concerns emerge regarding long-term financing mechanisms, supply chain reliability, and human resource capacity at the district level. The paper concludes with evidence-based policy recommendations organized across five domains: strengthening intersectoral governance through dedicated coordinating bodies; investing in cold chain infrastructure and local food procurement systems; developing comprehensive nutrition literacy programs for parents and communities; establishing robust monitoring and evaluation frameworks with real-time data systems; and creating sustainable financing models that balance national budgets with district-level implementation costs. These recommendations emphasize the imperative of contextualizing global nutrition interventions within Indonesia's unique geographic, cultural, and institutional landscape while maintaining the program's core commitment to equity and dignity for all children.